Comparativo de rendimiento y otras caracteristicas biométricas de dicinueve híbridos de maíz (Zea mays L.) Amarillo duro en el Valle de CHAO, LA LIBERTAD” - Vásquez Pérez, Patricia Johana (2013)
This field research was carried out from January to July 2008 in San Francisco del Lunar, Chao district, province of Virú, La Libertad department, Peru. The main goal was to settle and compare the yield and the performance of nineteen hybrids of flint and dent corn. The genetic material was fifteen experimental hybrids and four commercial hybrids, distributed in a complete blocks design with four replications. The furrows were 4,4 long; 0,8 width, and two seeds were sowed at 0,4 row spacings. The soil texture was clay loam, the content of organic material and phosphorus was low, high potassium, and a moderately alkaline pH. The average temperature was 21,13Cº, and relative humidity was 90, 18%. The characteristics evaluated were: yield, number of ears per hectare, number of ear per plant, ear weight, male an female flowering , hundred seeds weight, kernel weight, plant height, ear height, stalk diameter, foliage area of the leaf below the first ear, ear length, ear diameter, number of rows per ear, number of grain per row. The outstanding hybrid for grain yield was Dekalb 5005 with 8,59 t.ha-1 followed by the group formed with Exp-PM-12, Exp-PM-1, Exp-PM-13, Exp-PM-10, Exp-PM-15, Exp-PM-7, Exp-PM-3, Exp-PM-14 Exp-PM-11, Exp-PM-2, Exp-PM-8, XB-8010, PM-212 and AG-001 which were statistically the same with values from 5,82 to 7,16 t.ha-1. In the lowest group for plants height, there were found XB-8010, AG-001, Dekalb 5005 and Exp-PM-11. They showed a range of values ranged from 2, 60 m to 2, 84 m. On the other hand, the hybrids Exp-PM-4, Exp-PM-1, Exp-PM-15, Exp-PM-2, Exp- PM-8 y PM 212 formed the statistically group for the highest plant height. Dekalb 5005 and experimental PM-11 were 16.6 and 15.3 rows per ear. They formed the group statistically superior, in number of kernels per row were outstanding hybrids: Dekalb 5005 was 40.5; AG.001 with 37.9, the experimental PM-7 with 37.8 and experimental PM-10 with 37.1 kernels per row. The average length of the cob in the hybrids was 17.85 cm. Moreover, the resulting hybrids have less wide cobs were Exp-PM-7, Exp (30x35) with a value of 3.20 and 3.19 cm respectively. In number of rows per ear stands Dekalb 5005 with 16.6 followed by the Exp-PM-11 with 15.3, also Dekalb 5005 was the hybrid statistically superior for number of kernels per row with 40.5 followed by AG-001 with 37.9.